Studying the Elimination Pattern of Caprine Arthritis Encephalitis Virus in the Milk of Infected Females - Gaeta, Natália Carrillo; Hasegawa, Marjorie Yumi; Ribeiro, Bruno Leonardo Mendonça; Gomes, Ana Lisa; Castro, Roberto Soares; Gregory, Lilian (Acta Scientiae Veterinariae, 2016)
Background: Small ruminants can be infected by lentiviruses, such as Maedi-Visna Virus (MVV) and Caprine ArthritisEncephalitis Virus (CAEV). The main route of transmission is via ingestion of contaminated colostrum and milk although vertical transmission can occur. Recently, several studies for molecular detection of CAEV in milk, using conventional PCR and real-time PCR are being carried out. Considering the elimination of CAEV through the milk of infected animals and the importance of this virus in the goat production, the aim of this study was to evaluate the elimination pattern of CAEV in milk, evaluating the frequency and the concentration eliminated during the lactation. Materials, Methods & Results: A cohort of four negative females for CAEV was inseminated with semen experimentally infected with CAEV-Cork strain. They were located in stalls at the Hospital of Ruminants from School of Veterinary Medicine and Animal Science from University of São Paulo, Brazil. Goats received coast-cross hay, pellet feeding, mineral salt and water ad libitum. All females were observed every day during pregnancy. After lambing, kids received warm bovine colostrum and bovine milk powder during two months. Forty milk samples were collected at five-day interval during two months. A mixture of five milliliters from each teat was obtained and cDNA extraction was performed using DNA Mini Kit. Initially, real-time PCR was performed using an endogenous control for research of the constitutive gene (12S) for goats. Using positive samples in the first reaction, another reaction was performed using specific primers for lentiviruses based on the gag gene (conserved in retroviruses). In order to compare the results, nested-PCR was performed. After realtime PCR, cDNA was detected in samples from one female, corresponding to the day of calving, 14th, 20th, 25th, 35th and 40th day postpartum (15%; 6/40). The absence of amplified cDNA in thirty days postpartum, as well as in the final twenty days of lactation, was observed. Sample corresponding to the 7th day postpartum was not obtained. The virus concentration throughout lactation grew up until forty days postpartum. After this period, there was no cDNA amplification. In Nested PCR, positive results were detected in samples corresponding to the day of calving, 15th days, 20th days and 30th days postpartum, only. Discussion: cDNA was detected in samples from one positive female, during forty days postpartum, but not on the 30th. On the other hand, amplified cDNA was observed on 30th day by nested-PCR. In this case, a false negative result was observed after real-time PCR, probably because sample corresponding to 30th days may not have been properly homogenized, so that the fraction used in real-time PCR was not representative. A higher number of positive samples were expected due to the higher sensitivity of the technique used. The low viral concentration in the milk due to high antibody titers, for example, leaded to a small number of cells containing the agent, reducing the possibility of detection. cDNA was not detected in any sample from three infected females. A possible false-positive serological reaction or the very low viral concentration in milk samples could explain the negative results, although some animals might be infected by a strain that could not be recognized by PCR.